LEGAL-LINGUISTIC PROFILING IN INSTITUTIONAL CONTEXTS: THE CASE OF EU STAFF REPRESENTATION BODIES - ROBERTSON, Colin D. (Comparative Legilinguistics, 2019)
This paper applies a structured legal-linguistic profiling approach to EU “staff representation bodies” as a way to access domains that lie behind the public face of EU institutions and their texts concerning translation, language and terminology. The study commences with a legal-linguistic analysis of EU texts for references to “staff”, “staff representation” and “employment” in order to identify specific texts and bodies of relevance to the study. This approach leads to two broad categories: staff committees and trade unions. Information is sought from EU institutions about these bodies and their translation and language arrangements, and a list is made of websites available to the general public. These sites are then examined as part of the legal-linguistic profiling approach.